Familial Gigantiform Cementoma: Case Report of an Unusual Clinical Manifestation and Possible Mechanism Related To "Calcium Steal Disorder". Issue 9 (March 2016) - Ma, Chunyue; Wang, Hongwei; He, Guang; Qin, Xingjun
Abstract : Abstract: Familial gigantiform cementoma is an exceedingly rare but distinct subtype of cemento-osseous-fibrous lesion. Undocumented radiographic changes and related bone metabolism disorder are herein hypothesized and discussed. We present an adolescent case with recurrent familial gigantiform cementoma who received surgical intervention in our hospital. Apart from typical multiquadrant and expansile abnormalies involving both jaws, he also suffered from several times of fractures in lower extremity. Furthermore, radiographic examinations of calvaria, pelvis, femoris, tibia, and fibula all revealed radiolucent areas signifying diffuse osteopenic bone losses. Some of his consanguineous relatives bore the same burden of fractures during pubertal period. Considering these polyostotic conditions, a correlation of congenital bone metabolism disorder in cases with familial gigantiform cementoma, named "calcium steal disorder, " was thus proposed. Familial gigantiform cementoma is closely associated with "calcium steal disorder." Whole-body dual-energy absorptiometry should be considered as a routine examination for fracture-related risk prediction.